Diffuse Esophageal Leiomyomatosis in Pediatric Patients: A Systematic Review and Quality of Evidence Assessment - Ziogas, Ioannis A.; Mylonas, Konstantinos S.; Tsoulfas, Georgios; Spartalis, Eleftherios; Zavras, Nikolaos; Nikiteas, Nikolaos; Schizas, Dimitrios (European Journal of Pediatric Surgery, 2019)
Background Diffuse esophageal leiomyomatosis (DEL) is a rare disorder characterized by benign hypertrophy of esophageal smooth muscle cells. No rigorous summary of available evidence on how to best manage these patients exists.Objective To define the clinical features and outcomes of pediatric patients with DEL.Materials and Methods A systematic literature search of the PubMed and Cochrane databases was performed with respect to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (end-of-search date: October 6, 2018). The algorithm: “esophageal leiomyomatosis AND (children OR pediatric*)” was implemented.Results Thirty-five studies including a total of 58 patients were analyzed. The female:male ratio was 1.45:1. Mean patient age was 8.54 ± 4.67 years. The most common disease manifestations were dysphagia and gastrointestinal symptoms (90.0%, 95% confidence interval [CI]: 78.2–96.1), followed by failure to thrive (57.9%, 95% CI: 36.2–76.9) and pulmonary symptoms (56.4%, 95% CI: 41.0–70.7). Alport syndrome (AS) was seen in 57.7% (95% CI: 44.2–70.1) of the patients. The most commonly implemented procedure was esophagectomy (85.2%; n = 46/54; 95% CI: 73.1–92.6) with gastric transposition (37.8%; n = 17/45; 95% CI: 25.1–52.4). Postoperative complications developed in 33.3% (n = 15/45; 95% CI: 21.3–48) of the patients. All-cause mortality was 7.0% (95% CI: 2.3–17.2) and disease-specific mortality was 3.5% (95% CI: 0.3–12.6).Conclusion DEL is an uncommon condition that typically occurs in the setting of AS. Esophagectomy with gastric transposition is the mainstay of treatment. Although complications develop in one-third of the patients, mortality rates are low.
Keywords: pediatric surgery; diffuse esophageal leiomyomatosis; Alport syndrome; esophageal neoplasms; esophageal tumors